Analysis of M-Banking Adoption on Banking Performance Listed on the Indonesian Stock Exchange - Nengsi Sudirman; Maria Natalia Wainip Epin; Waode Rizky Amalia (PT FORMOSA CENDEKIA GLOBAL, 2023)
The banking industry is one that has adopted information technology. The purpose of this study is to determine the effect of using m-banking on the performance of banks listed on the Indonesia Stock Exchange in 2022. The population data used in this study are all banks listed on the Indonesia Stock Exchange, of which 46 companies are listed. Samples were selected by purposive sampling. To analyze the effect of mobile banking on the performance of the corporate banking sector, multiple regression equation analysis tools are used to include two control variables, namely company size using the normal logarithm of total assets and credit risk (NPL) with ROA as a measure of bank performance. The results of the study show that the use of mobile banking has a positive effect on ROA. Bank size (SIZE) has a negative effect on ROA. The larger the size of the bank, it will reduce the performance of commercial banks in Indonesia. NPL has a negative effect on ROA. Increasing credit risk or increasing the NPL value will reduce bank profitability